On evil, providence, and freedom: a new reading of Molina - Wiebe, Mark B. (Northern Illinois University Press, 2017)
Molina and the battle over divine foreknowledge and human freedom -- The concord of grace and free will: Thomas Aquinas and Luis de Molina on God's nature and providence -- Anti-Molinism -- Freedom, divine foreknowledge, and the problem of evil